Reversal of multidrug resistance by magnetic Fe3O4 nanoparticle copolymerizating daunorubicin and 5-bromotetrandrine in xenograft nude-mice - Baoan Chen (Dove Medical Press, 2009)
Baoan Chen1,* Jian Cheng1,* Yanan Wu1, Feng Gao1, Wenlin Xu2, et al 1Department of Hematology;2Department of Hematology, The Affiliated People’s Hospital, Jiangsu University, Zhenjiang, PR China *These authors have contributed equally to this workAbstract: In this paper we establish the xenograft leukemia model with stable multidrug resistance in nude mice and to investigate the reversal effect of 5-bromotetrandrine (5-BrTet) and magnetic nanoparticle of Fe3O4 (MNP-Fe3O4) combined with daunorubicin (DNR) in vivo. Two subclones of K562 and K562/A02 cells were inoculated subcutaneously into the back of athymic nude mice (1 × 107 cells/each) respectively to establish leukemia xenograft models. Drug-resistant and sensitive tumor-bearing nude mice were assigned randomly into five groups which were treated with normal saline; DNR; NP-Fe3O4 combined with DNR; 5-BrTet combined with DNR; 5-BrTet and MNP-Fe3O4 combined with DNR, respectively. The incidence of formation, growth characteristics, weight, and volume of tumors were observed. The histopathologic examination of tumors and organs were detected. For resistant tumors, the protein levels of Bcl-2, and BAX were detected by Western blot. Bcl-2, BAX, and caspase-3 genes were also detected. For K562/A02 cells xenograft tumors, 5-BrTet and MNP-Fe3O4 combined with DNR significantly suppressed growth of tumor. A histopathologic examination of tumors clearly showed necrosis of the tumors. Application of 5-BrTet and MNP-Fe3O4 inhibited the expression of Bcl-2 protein and upregulated the expression of BAX and caspase-3 proteins in K562/A02 cells xenograft tumor. It is concluded that 5-BrTet and MNP-Fe3O4 combined with DNR had a significant tumor-suppressing effect on a MDR leukemia cells xenograft model.Keywords: 5-bromotetrandrine, magnetic nanoparticle of Fe3O4, multidrug-resistance, xenograft model